Parameter screening of a VPSA cycle with automated breakthrough control for carbon capture. (1st May 2023) - Gutierrez-Ortega, A.; Melis, A.; Nomen, R.; Sempere, J.; Fernandez-Garcia, J.; Pou, J.O.; Gonzalez-Olmos, R.
Graphical abstract: Highlights: A new automated breakthrough control for VPSA in carbon capture was studied. Vacuum pressure and the feed and rinse stop points were critical control variables. A CO2 stream with a purity of 98% and a recovery of CO2 of 81% were obtained. The productivity obtained was 0.26 kgCO2 /(kgads ·h). The energy consumption obtained was 0.18 kWh/kgCO2 . Abstract: Vacuum pressure swing adsorption (VPSA) is an efficient technology that can be used for carbon capture from combustion stationary sources. However, VPSA is a cyclic and complex process that involves several operational variables that can have an influence on the key performance indicators: purity, recovery, productivity, and energy consumption. Typically, the concentration of carbon dioxide (CO2 ), flowrate and gas temperature may vary depending on the excess of air on the combustion process, type of fuel, purity of the fuel, the efficiency of the combustion equipment, the energetic demand, among many other. An industrial CO2 capture technology must be able to adapt to these possible process changes. In this work, a new automated control strategy was applied, instead of using the conventional time scheduling, in a seven-step VPSA process for CO2 capture. The column breakthrough points were used to control the feeding, rinse and purge steps (stop points) together with three flowrates used in these steps and the vacuum pressure used in the regeneration step. A two-level fractional factorial design 2 7−3, was used to study the influence of these control variables on the key performance indicators, applying the analysis of variance (ANOVA). The results show that the critical parameters of this new control strategy were the vacuum pressure and the feed and rinse stop points. With the automated breakthrough control, it was possible to capture 81 % of the CO2 from a simulated dry flue gas obtaining a CO2 purity of 98 %, a productivity of 0.26 kgCO2 /(kgadsorbent ·h) and an energy consumption of 0.18 kWh/kgCO2 .